Faktor yang mempengaruhi pertumbuhan dan perkembangan tanaman berdasarkan perspektif Al- Qur’an - Ardiansyah, Moch Syaddad (Maliki Interdisciplinary Journal, 2023)
Science is the result of human thinking with an Islamic vision behind it. Science can be defined as a human product in the world. The principles of Islamic science must correspond to the ontological, axiological principles. The subject is the process of growth and development of the soil If the environment has a minimum temperature, then the plants do not grow. Allah Subhanahu waTa’ala says in Surah al-Jatsiyah verse 5, which means "And alternating with night and day and with the rain that God sends down from the sky, He revives the earth with rainwater after its death; and the turning of the wind are signs (of God’s power) to men who have understanding." In each environment, various plants are born and spread throughout the world, which are able to grow together at the temperature of that environment in pure sincerity.